British Idealist Aesthetics, Collingwood, Wollheim, And The Origins Of Analytic Aesthetics - Chinatsu Kobayashi (Baltic International Yearbook of Cognition, Logic and Communication, 2008)
Although Great Britain is the country of some of the earliest contributors to aesthetics as an independent philosophical discipline the subject attracted little interest in philosophical circles towards the turn of the twentieth century. In this paper, I shall focus on Bosanquet and Collingwood. In particular, as we shall see, Collingwood is often dismissed as having held an indefensible, outmoded ‘ideal’ theory, according to which the work of art is primarily ‘mental’, while his potential role in current debates is simply ignored. I will argue that this view is largely mistaken.
Keywords: philosophy; analytic philosophy; history of philosophy; aesthetics